Assessment of the fluid-dynamic and acoustic behaviour of a swirl static mixer for after-treatment systems. (15th January 2022) - Torregrosa, A.J.; Broatch, A.; Quintero, P.; Redondo, Á.; Morin, F.
Abstract: An investigation on the acoustic transmission loss and the pressure drop caused by a mixer inducing element located downstream of a Diesel Exhaust Fluid (DEF) injection port was carried out in order to reduce the knowledge gap identified for this kind of after-treatment system elements. Transmission Loss measurements were performed at 4 mass flow rate conditions; 0, 100, 200 and 300 kg/h. Additionally, pressure drop measurements were registered for a range of mass flow rates, from 0 to 800 kg/h at steps of 50 kg/h, with similar flow and room temperatures. The post-processing and analysis included the application of a decomposition technique in the case of the transmission loss, which lead to understand the contribution of reflective and dissipative effects to the total attenuation. Reference results are provided for the particular geometry and kind of mixer element characterized, as well as the full extent of the results analysis and the insights of the decomposition analysis technique, and also different modelling possibilities have been explored. The conclusions indicate that, while usually overlooked, these devices may have a significant influence on the exhaust acoustics, mainly due to the influence of their presence on the attenuation of the after-treatment device as a whole.